Treatment and prevention of infectious complications at various stages of reconstructive surgery - I. A. Filatova; S. A. Shemetov; Yu. P. Kondratyeva (Российский офтальмологический журнал)
Purpose. To evaluate the effectiveness and safety of monotherapy and combination therapy with Moxifloxacin-Optik and Mitraseptin-OphthalmoLOR drugs for the treatment of infectious complications after reconstructive operations on the accessory apparatus of the eye performed for congenital, post-traumatic, and senile pathology. Material and methods. 90 patients aged 18 to 75 years (M = 58.46 ± 7.31) with various pathologies of the auxiliary apparatus of the eye — 21 men (23.3 %) and 69 women (76.7 %) were included in the study. At the screening stage, 31 patients who showed signs of bacterial conjunctivitis were given a 7-day mono- or combined antimicrobial therapy, followed by an efficacy control according to bacteriological testing data. After 1 month, all 90 patients were divided into three groups depending on the therapy regimen. Group 1 (n = 30) had monotherapy with Moxifloxacin-Optik which started after the surgery and lasted up to 14 days. Group 2 (n = 30) had sequential therapy with Mitraseptin-OphthalmoLOR for 3 days before surgery and with Moxifloxacin-Optik for up to 14 days after surgery. Group 3 (n = 30) received combination therapy: Mitraseptin-OphthalmoLOR for 3 days before surgery and Mitraseptin-OphthalmoLOR + Moxifloxacin-Optician for up to 14 days after surgery. All patients had reconstructive plastic surgery on the auxiliary apparatus of the eye and underwent a standard ophthalmological examination before surgery and 3, 7 and 15 days after it. Results. All antimicrobial treatment plans showed high clinical effectiveness in the operated patients. The combined therapy with the antiseptic Mitraseptin-OphthalmoLOR and the antibiotic Moxifloxacin-Optik which brought about the greatest degree of eradication of conjunctival microorganisms (up to 100 %), has a pronounced antimicrobial effect, effectively controls the inflammation and reduces the therapy duration by 36 %, ensuring the best clinical tolerability. Conclusion. The use of various methods of antibiotic prophylaxis reduced the amount of bacterial microflora of the conjunctiva. The most effective method of preventing postoperative infectious complications is combined therapy with an antiseptic and an antibacterial drug.